Recycling and performance of thermoplastic composites under static loading - Ong, Nicxon Si En (Nanyang Technological University, 2024)
Thermoplastic composites (TPC) are gaining popularity in aerospace and automotive and many other industries. This is because of TPCs unique combination of properties including low density, high stiffness and strength that are comparable to high performance materials such as metal alloys. TPCs also offer many other advantages including high customizability, impact resistance and excellent chemical resistance. The increasing popularity in TPCs is leading to high production rates which leads to huge amounts of waste throughout the products’ lifetime. Conventional methods of TPC waste disposal bring severe environmental harm and are economically wasteful for industries. Recycling TPCs is an effective way to address these issues. This project’s aim is to improve the recycling process of TPCs in terms of efficiency and mechanical aspects. Carbon fiber-polyamide 6 (CF-PA6) TPC was specifically fabricated, recycled, tested and studied in this report due to its rising popularity in the aerospace and automotive industries. The pristine CF-PA6 parts were fabricated through sequence stacking and followed by a hot compression process. The waste from pristine CF-PA6 was collected and recycled. The recycling process was modified and executed multiple times with the goal of achieving a mechanically stronger recycling product while still considering the process efficiency. The recycling process led to 6 batches (random, long-8gPA6, long-16gPA6, square-8gPA6, long-8gPA6-1CF, long8gPA6-2CF). The pristine and recycled TPCs were then statically tested and showed that longitudinal columns of CF-PA6 with 8g of pristine PA6 and 1 CF fabric provided the best flexural properties with 318.5 MPa and 26336.5 MPa for flexural strength and flexural modulus respectively. In terms of percentage loss with respect to pristine, the percentages are 40.6% and 62.5% respectively. The test also showed that longitudinal columns of CFPA6 with randomly laid PA6 mixed with carbon fiber provided the best compression properties with 88.0 MPa, 88.2 MPa and 3074.2 MPa for compression strength, yield strength and modulus of elasticity respectively. In terms of percentage loss with respect to pristine, the percentages are 17.7%, 15.5% and 37.4%. The results showed that longitudinal columns of recycled CF-PA6 was the better configuration to attain good mechanical properties. It was also the easier and faster configuration to recycled CF-PA6. It was also concluded from the flexural and compression test results that adding too much pristine PA6 into the recycled parts decreases the mechanical properties of the recycled piece. The also results showed that adding pristine carbon fiber fabric will significantly improve only the flexural properties and not the compression properties.